Cytomegalovirus pouchitis in a patient with Crohn's disease. (17th July 2014) - Mabvuure, Nigel Tapiwa; Maclean, Laura; Oien, Karin; Gaya, Daniel
Abstract : Colectomy with ileoanal pouch formation is usually contraindicated in patients with Crohn's disease (CD) due to the risk of recurrent disease and pouch failure. We report the case of a patient, initially thought to have ulcerative colitis (UC), who underwent such surgery but subsequently developed perianal CD. She presented with diarrhoea and weight loss. Inflammatory markers were raised. Pouchoscopy revealed deep ulcers within the pouch. The main differential diagnoses were idiopathic pouchitis and recurrent CD. However, immunohistochemical staining demonstrated positivity for cytomegalovirus (CMV). Stool frequency, C reactive protein and albumin normalised within 48 h of starting oral valgancyclovir. At 15 weeks, pouch appearances were improved, no histological evidence of CMV was found and baseline pouch function had returned. This case highlights that CD can present many years after surgery for apparent UC. Also, CMV pouchitis should be considered as a differential cause of pouchitis especially as it is treatable with antiviral therapy.